Evaluasi Penggunaan Antibiotik Empiris dan Analisis Biaya Demam Tifoid di Sebuah RS Swasta Kota Semarang - Hananun Zharfa Hanifah; Ika Puspita Sari; Titik Nuryastuti (Fakultas Farmasi Universitas Andalas, 2018)
The treatment of typhoid, which is caused by S. typhi, requires wise use of antibiotics. The use of irrational antibiotics can increase mortality, morbidity, disease spread and health costs. This study aims to understand the appropriateness of antibiotics use in a private hospital Semarang, the relationship between antibiotics rationality and costs. An observational retrospective study that used a cross sectional method, whereby data was collected from medical records and financial recap that fulfil the inclusion criteria. Data were used to perform descriptive analysis, analysis of antibiotics rationality using the Gyssens method, and to study the relationship between rationality and healthcare costs. Data on rationality and costs were analysed using the Mann Whitney test. Result showed 180 cases were evaluated during this study: 98 antibiotic regimens from medication in hospitalized and 82 antibiotic regimens from medication through take-home medicines. A number of 20,4% of the cases from medication in hospitalized and 7,3% of the cases from medication through take-home medicines were considered rational. There is a relationship between antibiotics rationality and antibiotic costs (p<0,05)